Noise as music - RAKOWSKI, A. (Archives of Acoustics, 1996)
It cannot be denied that music and noise have some common features. Since sounds of nature and sounds of acoustic environment are sometimes perceived in an aesthetic mode like music, the fundamental questions arise: What is music? and: Can noise become music? To answer these questions several problems are briefly discussed. First, music is presented as a communication process where information about the sound structure is transmitted from Sender to Receiver basing on a communication code known to both participants. Recognition of the structure is a source of aesthetic pleasure and involves rich (mostly emotional) connotations. Next, examples are given of contemporary music in which sounds, previously considered as "non musical" play an essential part. Music of Italian Futurists and French "Musique Concrete" are described in more details.